Production of linear alpha olefin 1-octene through 1-octanol dehydration in packed-bed membrane reactors with large mesoporous membranes (PMRL) for remarkable improvement in 1-octanol conversion and 1-octene yield. (1st February 2023) - Lee, Dong-Wook; Jin, Min-Ho; Park, Ju-Hyoung; Lee, Young-Joo; Choi, Young-Chan; Kim, Young-Eun; Koo, Kee Young; Park, Ji Chan; Youn, Min Hye; Chun, Dong Hyun
Graphical abstract: There have been few publications showing the reactor structure as a strategy to enhance the efficiency of the alcohol dehydration. Here, we report a packed-bed membrane reactor with large mesoporous membranes (PMRL) as another solution to remarkable improvement in 1-octanol conversion and 1-octene yield of 1-octanol dehydration. The PMRL can be easily applied to any existing packed-bed reactors for dehydration or dehydrogenation reaction regardless of types of heterogeneous catalysts, because the existing catalysts are easily loaded on the membranes in the PMRL. Highlights: We report PMRL as another solution to improvement in performance of 1-octanol dehydration. Compared to PR, 1-octanol conversion and 1-octanol yield of PMRL increased by up to 21.3 and 16.4%. PMRL does not need a retentate side and sweeping. PMRL can be set up by only installing large mesoporous membranes in any existing PR. Various catalysts can be easily loaded on the membranes in PMRL. Abstract: In this study, we report a packed-bed membrane reactor with large mesoporous membranes (PMRL) as a solution to remarkable improvement in 1-octanol conversion and 1-octene yield of 1-octanol dehydration. Compared to the conventional packed-bed reactors (PR), 1-octanol conversion and 1-octanol yield of the PMRL increased by up to 21.3% and 16.4% in the temperature range of 340 °C–380 °C. The PMRL has simultaneously advantages of packed-bed reactors and membrane reactors. As the PMRL is equipped with large mesoporous membranes under a catalyst bed in the existing packed-bed reactors to achieve conversion enhancement like membrane reactors, the PMRL can be operated under ambient pressure without autogenous pressure in spite of the absence of a retentate side and sweeping gas which should be needed in the existing packed-bed membrane reactor equipped with dense, microporous, and mesoporous membranes because of autogenous pressure. Therefore, the PMRL can be easily applied to any existing packed-bed reactors for dehydration or dehydrogenation reaction regardless of types of heterogeneous catalysts, because the catalysts can be easily loaded on the membranes in the PMRL without the retentate side and sweeping gas.